Pressure‐activated microsyringe composite scaffold of poly(L‐lactic acid) and carbon nanotubes for bone tissue engineering. Issue 2 (26th July 2012) - Vozzi, Giovanni; Corallo, Claudio; Daraio, Chiara
Abstract Tissue engineering is an innovative interdisciplinary field in which bioengineers and life scientists try to regenerate and reproduce natural tissues through the use of biodegradable structures, called scaffolds, with the aim of mimicking the specific tissue extracellular matrix (ECM). Carbon nanotubes (CNTs) offer a natural platform for obtaining composite microfabricated scaffolds thanks to their excellent mechanical properties and their good biocompatibility. In this study, we microfabricated three‐dimensional (3D) scaffolds by mixing poly(L‐lactic acid) (PLLA) and multiwalled carbon nanotubes (MWCNTs) for bone tissue engineering. We measured their mechanical properties and studied their biocompatibility with human fetal osteoblasts (hFOB 1.19). The 3D microfabricated PLLA/MWCNTs nanocomposite scaffolds showed higher stiffness and cell viability than the pure 3D microfabricated PLLA scaffolds. The results of this preliminary work suggest that biopolymer/CNT microcomposites and nanocomposites could be used as effective building blocks to replace ECMs in bone tissue engineering applications. The final goal is the creation of innovative scaffolds for implants and tissue regeneration. © 2012 Wiley Periodicals, Inc. J. Appl. Polym. Sci., 2013